A novel testing system for hydromechanical investigation of rock materials in neutron and X-ray imaging instruments - Vieira Lima, Fernando; Hall, Stephen; Engqvist, Jonas; Tudisco, Erika; Woracek, Robin (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2024)
This article introduces a novel testing system for investigating rock hydromechanical behavior with neutron and X-ray imaging techniques. The system comprises four subsystems: an axial compression system, a confining pressure system, a fluid flow system, and a triaxial cell. In order to enable imaging with both modalities to track fluid flow and deformation in situ and 3D, the cell was designed to have sufficient transparency to X-rays and neutrons. The system's capabilities are demonstrated by showing neutron and X-ray tomography data of Idaho Gray sandstone samples during in situ coupled flow-triaxial tests. Quasi-single-phase flow analysis was enabled by directly visualizing the fluid front advance via neutron tomography by exchanging light water (H2O) and heavy water (D2O). Digital Volume Correlation (DVC) could be performed on both the X-ray and neutron tomography images to quantify the mechanical strain field evolution in the samples, which can be compared to the evolution of the fluid flow fields. In addition, the cell and a sample of Idaho Gray sandstone were imaged in a laboratory X-ray tomography machine, generating 3D reconstructed volumes with grain-scale resolution. Improvements are proposed for future experiments to obtain grain-scale resolution images during coupled flow-triaxial tests using neutron and X-ray beams simultaneously and conducting in situ experiments on laboratory tomographs. •A novel system for conducting flow and triaxial tests with neutron and X-ray imaging.•The triaxial cell is sufficiently transparent to both X-rays and neutrons.•3D flow path tracking can be achieved using high-speed neutron tomography.•Digital volume correlation can be performed from X-rays and neutron images.